2012
DOI: 10.1111/j.1574-695x.2012.00945.x
|View full text |Cite
|
Sign up to set email alerts
|

Human platelets efficiently kill IgG-opsonizedE. coli

Abstract: Platelets are known contributors of hemostasis but have recently been shown to be important in inflammation and infectious diseases. Moreover, thrombocytopenia is often observed in patients with sepsis. We previously reported that platelets actively phagocytosed IgG-coated latex beads. In the current study, the capacity of human platelets to participate in host defense against bacterial infections was determined by assessing their ability to kill E. coli. Washed human platelets were incubated with unopsonized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 28 publications
(44 reference statements)
1
46
0
2
Order By: Relevance
“…Aggregated IgGs [16] Mouse anti-human platelet mAb [30] Influenza virus H1N1 [16] Influenza virus H1N1 [16] Aggregated IgGs [16] HIT ICs [100] Anti-CD40L mAb + CD40L [75] Aggregated IgGs [19] IgG-coated beads [18] Escherichia coli [69] Fig. 3.…”
Section: Arachidonic Acid Metabolism (Thromboxane Production)mentioning
confidence: 99%
“…Aggregated IgGs [16] Mouse anti-human platelet mAb [30] Influenza virus H1N1 [16] Influenza virus H1N1 [16] Aggregated IgGs [16] HIT ICs [100] Anti-CD40L mAb + CD40L [75] Aggregated IgGs [19] IgG-coated beads [18] Escherichia coli [69] Fig. 3.…”
Section: Arachidonic Acid Metabolism (Thromboxane Production)mentioning
confidence: 99%
“…Platelets also bind various pathogens, including HIV and Staphylococcus aureus . Although not considered to be professional phagocytes, platelets are capable of internalizing targets, resulting in the killing of various bacterial species, including Escherichia coli and S. aureus . In addition to their direct bactericidal activities, platelets can affect both innate and adaptive immune responses through interactions with various types of leukocytes, most notably neutrophils .…”
Section: Introductionmentioning
confidence: 99%
“…The combined importance of platelet FcγRIIA and anti‐PF4/P IgG is further clear from work by Riaz et al ., who reported that both unopsonized and IgG‐opsonized E. coli bacteria could associate with platelets, but only IgG‐opsonized E. coli were efficiently killed by platelets . The bactericidal activity was dependent on FcγRIIA, was sensitive to cytochalasin D and was not a result of reactive oxygen metabolites.…”
Section: The Fcγriia and Platelet–bacteria Interactionsmentioning
confidence: 99%